Pollutants Removal from Contaminated Water using Agricultural Tea Waste (Camellia Sinensis) - Low, Wen Pei; Chang, Fung Lung; Siow, Jia Min (INTI International University, 2019)
The use of natural waste material as an alternative media for treating contaminated river water has gain more popularities in recent years since it is generally low cost and environmentally friendly. This is in line with the 3R campaign promoted by the National Solid Waste Management Department in Malaysia, aiming to overcome the landfill disposal issues. This study presents the investigation of heat-treated tea waste and acid-treated tea waste as an adsorbent to reduce the Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Total Nitrogen (TN) and Total Phosphorus (TP) occurring naturally in contaminated water. The contaminated water sample used in this study was circulated in a prototype to pass through the treated tea waste for five consecutive days. The water parameters were tested in accordance to the APHA method, which were later analysed and compared by evaluating the adsorption capacity, percentage removal of each pollutants and kinetic order reactions. It was identified that two different pre-treatment tea waste follow closely to the pseudo-second-order model due to chemisorption. The results show that the removal of BOD, COD, TP, TN, and TSS by using acid-treated tea waste were 38%, 35%, 68.38%, 42.36%, and 96.31% respectively. Comparatively, heat-treated tea waste was found to be only effective in removing TP, TN, and TSS, with a percentage removal of 53.91%, 78.22%, and 86.84% respectively. Overall, the finding of the study indicates that acid-treated tea waste is potential to be used as a low-cost adsorbent to reduce organic matter, nutrients, and suspended solids in contaminated water.